Triacylglycerols Composition and Volatile Compounds of Virgin Olive Oil from Chemlali Cultivar: Comparison among Different Planting Densities - Mokhtar Guerfel; Mohamed Ben Mansour; Youssef Ouni; Flamini Guido; Dalenda Boujnah; Mokhtar Zarrouk (The Scientific World Journal)
The present study focused on the comparison the chemical composition of virgin olive oil samples obtained from fruits of the main Tunisian olive cultivar (Chemlali) grown in four planting densities (156, 100, 69, and 51 trees ha−1). Despite the variability in the triacylglycerols and volatile compounds composition, the quality indices (free fatty acids, peroxide value, and spectrophotometric indices K232 and K270) all of the virgin olive oils samples studied met the commercial standards. Decanal was the major constituent, accounting for about 30% of the whole volatiles. Moreover, the chemical composition of the volatile fraction of the oil from fruits of trees grown at the planting density of 156, 100, and 51 trees ha−1 was also characterised by the preeminence of 1-hexanol, while oils from fruits of trees grown at the planting density of 69 trees ha−1 had higher content of (E)-2-hexenal (20.3%). Our results confirm that planting density is a crucial parameter that may influence the quality of olive oils.